Indonesian Fundamentalism? - Jamhari, Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
Islam in Southeast Asia provides an example of how a religion develops within a community with a wide variety of ethnic groups. Instead of pushing the local cultures and traditions aside, Islam opens up itself to them and incorporates them into the web of universal Islam. Now one can see the difference of Islamic expressions in Melayw, Aceh, Bugis, Banten, Java, Bugis, Sunda, Patani, Mindanau, Brunai, etc.DOI: 10.15408/sdi.v9i3.664